Republic of Moldova : Staff Report for the 2003 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2004)
Moldova showed reasonable macroeconomic developments. Executive Directors welcomed this development, and stressed the need to implement prudent macroeconomic policies and accelerate structural reforms to sustain growth. They encouraged fiscal and tax reforms, and urged the need to tighten monetary stance. They supported the Economic Growth and Poverty Reduction Strategy Paper (EGPRSP) and encouraged the authorities to include policies for improving the business environment and governance. They analyzed that the Ex Post Assessment contained a balanced analysis of the country's performance under the IMF assistance.